Education on Safe and Halal Cosmetics at SMK Swadaya Global School, East Jakarta: Edukasi Kosmetika Aman dan Halal di SMK Swadaya Global School Jakarta Timur - Hariyanti; Gantini, Sri Nevi; Fatmawati, Sofia; Supandi; Nining; Amalia, Anisa; Oktafiani, Erna; Dewi, Elvira Ratna (Jurnal Abdita Naturafarm, 2025)
The low level of awareness among Muslims regarding the use of safe and halal cosmetics necessitates public awareness education. The purpose of this activity is to educate partners to recognize and choose safe and halal cosmetics, while also becoming agents of change for families or relatives by providing accurate information in choosing safe and halal cosmetics. The educational method is carried out in the form of lectures and simulations of halal cosmetic products. The stages include: pre-test, counseling, simulation, and post-test. Evaluation of the activity is carried out by measuring the level of knowledge and achievement of predetermined objectives. Students demonstrated enthusiasm and active involvement during the activity. The analysis results show an increase in knowledge of the Medium Level from before (40%) and after (60%) the activity. In addition, direct observation also indicates an increase in involvement and deeper understanding among participants. Based on this, it is concluded that education through lectures and simulations introducing safe and halal cosmetics can improve the understanding of students at SMK Swadaya Global School in East Jakarta.